Market reactions to financial and resources BEE deals on the JSE - Hertz, Jenna (My University, 2019)
In South Africa, Black Economic Empowerment (BEE) has been instrumental in the transformation of the country post-Apartheid. The involvement of key sectors in transformation is dependent on specific Industry Charters and the impact of these charters on the implementation of BEE by companies has been largely ignored by prior literature. This research examines the short-run impact of BEE equity/ownership deals on the share price performance of JSE-listed stock by calculating abnormal returns (ARs) and cumulative abnormal returns (CARs) subsequent to announcements in the resource and financial sectors. The objective of the study is to determine whether announcements of BEE deals resulted in the creation of shareholder wealth in these specific sectors. The study further explores whether size of the issuing company was a factor in how the markets received BEE deal announcements. The research employed a standard event study methodology which is widely used in finance literature to examine the impact of corporate events on shareholder wealth. The sample included 111 BEE deal announcements by resource sector companies during the period January 2003 until October 2018 and 75 BEE deal announcements by financial companies during the period January 2004 until October 2018. ARs and CARs were analysed over an 11 day event window. The results of the study found that qualifying announcements had a significant positive impact on the CARs of financial sector companies and an insignificant negative impact on the CARs of resource companies over the 11 day event window. This demonstrated that BEE deals were perceived to destroy value in the resource sector and create value in the financial sector for shareholders. The difference in reaction between the two sectors was found to be significant. Furthermore, the research findings indicated that the market reacted more favourably to BEE deal announcements made by ‘small’ companies regardless of the sector. However, while these findings were significant for the financial sector, they were proven to be insignificant for the resource sector.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Commerce in Accountancy Johannesburg, 2019
Keywords: UCTD; Black Economic Empowerment (BEE); Event Study; Abnormal Returns; JSE; Resource sector; Johannesburg Stock Exchange; Business enterprises Black--South Africa; Options (Finance)--South Africa; SDG-8: Decent work and economic growth